Estudo sobre a viabilidade de projetos de comunicações de dados ou voz - Tamarozi, Giuliano Casa [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
It is hard to imagine the modern world without the facilities provided by telecommunications. These are the technological basis of modern societies as it's possible to define them as mass communications, really fast and essential to the globalized world market. Making information and use of telecommunications available is an ongoing challenge for companies concerned with both social and urban development, which is the basis of this work. In Brazil, as the telecommunications technology had been developing, it was evident that the challenge of providing a quality service for citizens was a burden too heavy for just one nation-sized enterprise; therefore, the technology and quality of services were hold for decades in comparison to other parts of the world. To answer this call of society and increase the quality of services, the state began to act only as a regulator, while local, regional and macro-regional companies emerged to fill the technological blank and backward technology left by the government. This work focuses on small businesses or individuals who aim to invest in the expansion of information transmission network without relying on companies already consolidated in the market. An introduction is written about basic issues in building networks and links for transmitting information and an initial evaluation of them. This evaluation should be considered the first step to the project due to numerous simplifications in the calculations. This simplification aims to ease the understanding of basic issues on the subject, emphasizing what was deemed essential. So, after the initial valuation of locations and technologies, a deeper study is needed to confront the original premise and effectively run the project. The values were combined with the project technical data to result in a numeric easy comparison of values, based on the year 2015... (Complete abstract click electronic access below)

É difícil imaginar o mundo contemporâneo sem as facilidades providas pelas telecomunicações. Estas são de fato, as bases tecnológicas das sociedades modernas já que se tratam de meios de comunicação em massa, extremamente ágeis, de grande abrangência e, consequentemente, intrínsecos aos mercados de capitais globalizados. Tornar a informação e uso das telecomunicações disponíveis é um desafio permanente para sociedades preocupadas tanto com o desenvolvimento social, quanto urbano. Este é o enfoque deste trabalho. No Brasil, conforme a tecnologia de telecomunicações se desenvolveu, foi evidenciado que o desafio de oferecer um serviço de qualidade para os cidadãos é um fardo muito grande para apenas uma empresa de porte nacional carregar e, como consequência, a tecnologia e a qualidade dos serviços no pais foram afetados durante décadas. Para aliviar esta pressão sobre a sociedade e aumentar a qualidade de serviços prestados, o Estado passou a atuar apenas como órgão regulador, enquanto, empresas locais, regionais ou macrorregionais surgiram para preencher o defasamento tecnológico deixado pelo governo. Este trabalho tem como foco as pequenas empresas ou indivíduos que almejam investir na expansão da rede de transmissão de informações sem depender de empresas já consolidadas de grande porte ou concessionárias. Uma introdução é realizada sobre assuntos básicos na construção de redes e enlaces para transmissão de informação e uma estimativa inicial dos mesmos. Esta estimativa deve ser considerada inicial devido a inúmeras simplificações a que o projeto em um primeiro momento exige, como por exemplo, o perfil topográfico somado às construções preexistentes nas localizações estudadas. Esta simplificação visa facilitar o entendimento de assuntos básicos sobre o tema, enfatizando o que foi julgado essencial... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Linhas de telecomunicação; Fibras oticas; Estações terrestres (Telecomunicação por satélite); Earth stations (Satellite telecommunication)